2014
DOI: 10.1002/mrd.22441
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress during in vitro fertilization decreases fertilization success by disrupting anti‐polyspermy systems of the oocytes

Abstract: Low pregnancy rates during the summer are due, in part, to reduced fertilization. Given that elevated temperature is associated with this season, we investigated the effect of heat stress during fertilization using an in vitro model. Three experiments were performed to determine the mechanism by which exposure to elevated temperature disrupts fertilization. Oocytes were fertilized for 6 hr at 38.5°C or 41.0°C or 40.0°C with non-pre-incubated sperm, or for 6 hr at 38.5°C with sperm that had been pre-incubated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 61 publications
0
31
0
1
Order By: Relevance
“…Intracellular ROS were immediately measured using fluorescent probes as previously described (Sakatani, Yamanaka, Balboula, Takenouchi, & Takahashi, ). Briefly, embryos were placed in PVP‐PBS containing 10 µM 2′, 7′‐dichlorodihydrofluorescein diacetate (DCHFDA; Molecular Probes, Eugene, OR) for 15 min at 38.5°C in a humidified atmosphere containing 5% CO 2 in the air and washed twice with PVP‐PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular ROS were immediately measured using fluorescent probes as previously described (Sakatani, Yamanaka, Balboula, Takenouchi, & Takahashi, ). Briefly, embryos were placed in PVP‐PBS containing 10 µM 2′, 7′‐dichlorodihydrofluorescein diacetate (DCHFDA; Molecular Probes, Eugene, OR) for 15 min at 38.5°C in a humidified atmosphere containing 5% CO 2 in the air and washed twice with PVP‐PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS were immediately measured using fluorescent probes as previously described (Sakatani, Yamanaka, Balboula, Takenouchi, & Takahashi, 2015). Briefly, embryos were placed in PVP-PBS containing…”
Section: Detection Of Oxidative Stress In Embryosmentioning
confidence: 99%
“…The in vitro maturation, fertilization, and culture procedures used in this study were performed as described previously (Sakatani, Yamanaka, Balboula, Takenouchi, & Takahashi, ). Briefly, ovaries were obtained from Japanese Black cows slaughtered at a local abattoir.…”
Section: Methodsmentioning
confidence: 99%
“…However, experiment work of Sakatani et al (2015), revealed that embryos that reached the blastocyst stage which were exposed to heat stress at the early stages of the oocyte does not affect the total cell number of the trophectoderm cell and the inner cell mass ratio any differently compared to the none heat shocked embryos during in vitro culture. Therefore, all these findings suggest that embryos that have passed through the effects of heat exposure might results in the reduction of cell nuclei number or restore a normal viability of nuclei cell number regardless of exposure to heat stress (Sakatani et al, 2004).…”
Section: Nuclei Cell Analysis Of Produced Blastocystmentioning
confidence: 98%